La incidencia de la biografía en el concepto hegeliano de experiencia: El caso de la hipocondría - Sisto, Horacio Martín (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: Here I argue that the concept of experience that Hegel presents in the Phenomenology is linked to his conception of the dynamics of intellectual and spiritual life as he lived it in his own life and he believed as reflected in the lives of other men. A particular phase of this dynamic is correlated to what medicine and a certain intellectual atmosphere of the time called ‘hypochondria.’ Because the incidence of the biographical in the phenomenological concept of experience is not obvious, the work is preceded by a series of general methodological elucidations about the relationship between experience and concept of biography (1). In order to provide the theoretical framework for the identification of one of its phases, I offer (2) a brief conceptual reconstruction of the concept of experience that emphasizes the logical structure (a), and another brief reconstruction of the same (b) highlighting the dramatic aspects of the concept. Then (3) I explain the link between the concept of experience and the phenomenon ‘hypochondria’ by the reference to letters, testimonials and reviews of the time (a, b, c), the concept of this phenomenon that Hegel offers in his Lectures (d), and a finer methodological and historical discussion that some specialists has developed around this linkage (e). I conclude the work (4) with a reference to the way Hegel philosophically considered biographical events.  KEYWORDS: Experience concept, Biography, Hypochondria.